To What Extent Are the Reports of Stock Analysts Useful? - Ebinesan, Noel Artputhan (2007)
Around the world, there are hundreds of thousands of stock analysts being employed to write research reports of firms (T. Green, 1). The information provided by sell-side analyst is myriad in nature. Though, one of the key tasks of analystÃÂÃÂ¢ÃÂÃÂÃÂÃÂs is to forecast earnings. Hence, the managers of funds need a guide as to the relative usefulness of these so that they are able to make investing decisions that are most effective possible. More precisely, firstly, they require knowledge concerning the degree of accuracy exhibited by them so that they are able to place the appropriate amounts of importance on them individually (Treynor et al., 1973). In terms of capital markets, it is vital to have knowledge pertaining to their accuracy because, as a result of, one is able to gauge the relative efficiency of capital markets. (Dimson et al., 1258) Hence, the purpose of my study, which is to evaluate the usefulness of sell-side analyst reports and as such, to go about undertaking this, the informational content within one of the summary measures was evaluated, namely earnings forecast. Furthermore the efficiency with which capital markets evaluate this information was evaluated as well. Lastly, the relative efficiency of stock markets was evaluated and thus the data from four countryÃÂÃÂ¢ÃÂÃÂÃÂÃÂs stock markets were used to evaluate this phenomenon, namely Malaysia, Singapore, Hong Kong and Thailand.